2017
DOI: 10.1097/igc.0000000000000971
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Prognostic Factors of Synchronous Endometrial and Ovarian Cancers—A Single-Institute Review of 43 Cases

Abstract: Women with synchronous primary endometrial and ovarian cancers are young, nulliparous, obese, and premenopausal and have a favorable overall prognosis. Grade 3 disease at both sites and presence of lymphovascular space invasion are independent prognostic factors for recurrence and survival, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
(26 reference statements)
2
19
1
3
Order By: Relevance
“…In a retrospective study in Japan, 2 of 23 patients with synchronous EC and OC experienced recurrence after adjuvant therapy, though none of 10 patients who did not receive adjuvant therapy had recurrence [23]. Studies on high-risk factors of recurrence may provide an index or indications for adjuvant therapy [24, 25]. Interestingly, concordant tumor grade was not associated with survival for stage I synchronous carcinomas in a large case–control study [10].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study in Japan, 2 of 23 patients with synchronous EC and OC experienced recurrence after adjuvant therapy, though none of 10 patients who did not receive adjuvant therapy had recurrence [23]. Studies on high-risk factors of recurrence may provide an index or indications for adjuvant therapy [24, 25]. Interestingly, concordant tumor grade was not associated with survival for stage I synchronous carcinomas in a large case–control study [10].…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to small sample size and high frequency of endometrioid endometrial and ovarian double primary cancer. This synchronous or metachronous endometrial and ovarian cancer is known to show endometrioid histological type in more than 50%–80% cases [ 34 35 36 ]. We had 7.0% (9/129 cases) of synchronous or metachronous endometrial and ovarian cancer in this research and it is similar to previous report that synchronous endometrial and ovarian cancer is account for 10% of all ovarian cancer patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, Scully proposed more detailed diagnostic criteria. Since the above criteria are widely used, there are many studies comparing the characteristics and prognoses in these two groups (MC and DPC) [4][5][6][7][8][9][10][11][12][13][14][15]. A prior study suggested that the prognosis was poor when metastasis involved other sites in addition to the uterus and ovaries and when there was no distinction between the DPC and MC [5].…”
Section: Introductionmentioning
confidence: 99%
“…Early-stage DPC showed a good prognosis in a study conducted only on DPC patients [10]. Song et al showed the association of the initial CA-125 level and ovarian stage with DPC survival [11], while Jain et al showed the association between lymphovascular invasion and DPC survival [12]. When comparing DPC with endometrial cancer, prognosis is not inferior than that in endometrial cancer [13].…”
Section: Introductionmentioning
confidence: 99%